The Philosophical Problem of Evil in the Intellectual System of Suhrawardī and John Hick - Zamzami, Mukhammad; Eskandian, Abdullah Hosseini; Muktafi, Muktafi; Mukaffa, Zumrotul (Jurnal Theologia, 2021)
The debate over the term “evil” is one of the most contentious issues in philosophy, as this term is considered to be antithetical to existence. Suhrawardī al-Maqtūl, a prominent Islamic theosophist, believed that evil did not exist. That which is considered evil or not evil is a suggestion for achieving good, and as such, it is also good. As a result, the term “crime” does not exist. What Suhrawardī said contrasted with John Hick’s view in the article “Theodicy of Soul Cultivation.” Hick concludes that basically evil exists, but only insofar as it is required to develop and evolve the human psyche and spirituality. After comparing the thoughts of these two figures, this article concludes that their partisan defence of God’s existence and His attributes regarding evil is what leads us to their views on the term “evil” and solutions to solve the crime. Suhrawardi and Hick both believe that the existence of evil does not preclude the existence of God because God is absolute. God is not against good or evil. What has considered evil is the judgment of one’s misunderstanding or the requirements for obtaining charity.